Should pension systems recognise "hazarduous and arduous work"? - Zaidi, Asghar; Whitehouse, Edward (Paris, 2009)
"Special pensions for workers in hazardous or arduous jobs have long been a feature of the pension landscape and, recently, they are the subject of a great deal of debate in the pension arenas of many OECD countries. Such pensions are historically rooted in the idea that people who work in hazardous or arduous jobs – say, underground mining – merit special treatment. The rationale for this scheme is that hazardous or arduous work increases mortality and reduces life expectancy, thus reducing the time during which retirement benefits can be enjoyed. This results in such workers being made eligible for earlier access to pension benefits than otherwise available in that country’s general pension scheme."